2006
DOI: 10.1007/s00411-005-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of deciduous molars in EPR dose reconstruction

Abstract: In the present study naturally loose deciduous molars were investigated. The feasibility of separating enamel from small size molars was analysed. EPR spectrum parameters of whole molars and separated enamel only were evaluated before and after laboratory irradiation. The Electron paramagnetic resonance (EPR) signal amplitudes of CO (2) (-) and native signals were determined by spectrum deconvolution, as a function of radiation dose in the range 0.1-10 Gy. A detection threshold of absorbed dose from deciduous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…El Faramawy and Wieser (2006). They concluded that deciduous tooth enamel is "similar" to permanent tooth enamel and deciduous teeth can thus be used for dosimetry purposes just like adult teeth.…”
Section: Epr Dosimetry With Primary Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…El Faramawy and Wieser (2006). They concluded that deciduous tooth enamel is "similar" to permanent tooth enamel and deciduous teeth can thus be used for dosimetry purposes just like adult teeth.…”
Section: Epr Dosimetry With Primary Teethmentioning
confidence: 99%
“…However, this different degree of microcrystal arrangement seems not to result in different radiation sensitivity. Using the additive dose method, El-Faramawy and Wieser (2006) have found that the detection thresholds and radiation sensitivities for deciduous teeth and permanent teeth are comparable.…”
Section: Epr Dosimetry With Primary Teethmentioning
confidence: 99%
“…Khan, et. al., 2004), other studies on the use of deciduous teeth have been performed (El-Faramawy, N.A., 2005, El-Faramawy, N., andWieser, A., 2006).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…(Brady, et al, 1968) Since this seminal description, substantial progress has been made in EPR dosimetry of in vitro samples and precision as fine as ±2.5 cGy has been reported for low-dose measurements, with precision of ±10% for doses above 25 cGy. (Chumak, et al, 2005) EPR tooth dosimetry using samples of pure enamel that have been extracted from irradiated subjects are typically performed at an X-band frequency (∼9 GHz) with a standard TE 102 cavity resonator and may employ a goniometer to average out spatial anisotropy (El-Faramawy and Wieser, 2006, Gualtieri, et al, 2001b, Hayes, et al, 2000, Hayes, et al, 1998. The high RF frequency and resonator filling factor contribute to the sensitivity of such measurements.…”
Section: Introductionmentioning
confidence: 99%